Effect of a chemically-modified-curcumin on dental resin biodegradation - Qi Dai; Hsi-Ming Lee; Austin Giordano; Fu-Pen Chiang; Stephen G. Walker; Rafael Delgado-Ruiz; Francis Johnson; Lorne M. Golub; Ying Gu (Frontiers in Oral Health)
IntroductionPrevious studies have shown Streptococcus mutans (S. mutans) esterase is a key mediator of dental composite biodegradation, which can contribute to recurrent caries. This study is to investigate the inhibitory effects of a novel Chemically-Modified-Curcumin (CMC 2.24) on esterase activities and related dental material biodegradation.MethodsDental adhesive materials and composite resins were incubated in S. mutans suspension with CMC 2.24 and other compounds, including doxycycline, Chemically-Modified-Tetracycline (CMT-3), and curcumin for 4 weeks. The pre- and post-incubation surface roughness were evaluated by either laser diffraction pattern and/or a 3D laser scanning microscope. Esterase enzyme inhibition assays were performed with the same test groups and activities were determined spectrophotometrically.ResultsAmong all experimental groups, CMC 2.24 significantly reduced surface roughness of dental composite (p < 0.01) and adhesive (p < 0.01) materials compared to bacteria-only group. Additionally, CMC 2.24 reduced porcine esterase activity by 46.5%, while other compounds showed minimal inhibition. In the S. mutans esterase assay, CMC 2.24 showed inhibition of 70.0%, while other compounds showed inhibition ranging from 19% to 36%.ConclusionOur study demonstrated that CMC 2.24 inhibited biodegradation of dental composite material more effectively than its mother compound, curcumin. Moreover, the mechanism of this biodegradation was likely mediated through bacterial esterase activity. Doxycycline achieved similar inhibition by completely eradicating S. mutans with its antibiotic action; hence, it is not recommended for long-term use.